Etiological Risk Factors for Sibling Incest: Data From an Anonymous Computer-Assisted Self-Interview. (October 2016) - Griffee, Karen; Swindell, Sam; O'Keefe, Stephen L.; Stroebel, Sandra S.; Beard, Keith W.; Kuo, Shih-Ya; Stroupe, Walter
Retrospective data from 1, 821 women and 1, 064 men with one or more siblings, provided anonymously using a computer-assisted self-interview, were used to identify risk factors for sibling incest (SI); 137 were participants in SI. In order of decreasing predictive power, the risk factors identified by the multiple logistic regression analysis included ever having shared a bed for sleeping with a sibling, parent–child incest (PCI), family nudity, low levels of maternal affection, and ever having shared a tub bath with a sibling. The results were consistent with the idea that SI in many families was the cumulative result of four types of parental behaviors: (a) factors that lower external barriers to sexual behavior (e.g., permitting co-sleeping or co-bathing of sibling dyads), (b) factors that encourage nudity of children within the nuclear family and permit children to see the parent's genitals, (c) factors that lead to the siblings relying on one another for affection (e.g., diminished maternal affection), and (d) factors that eroticize young children (e.g., child sexual abuse [CSA] by a parent). Thirty-eight of the 137 SI participants were participants in coerced sibling incest (CSI). In order of decreasing predictive power, risk factors for CSI identified by multiple logistic regression analysis included ever having shared a bed for sleeping with a brother, PCI, witnessing parental physical fighting, and family nudity. SI was more likely to have been reported as CSI if the sibling had touched the reporting sibling's genitals, and less likely to have been reported as CSI if the siblings had shared a bed.